STUDI KASUS : DUKUNGAN ORANG TUA UNTUK PEMANTAUAN PERKEMBANGAN ANAK USIA DINI MELALUI KPSP - Hatusupy, Chaterin; Ratulohain, Christina L (Poltekkes Kemenkes Maluku, 2024)
The World Health Organization revealed that around 43% or 250 million children in low-income countries experience problems in child growth and development. It is estimated that around 5-10% of children experience developmental deviations, but the main cause cannot be known for sure. For Indonesia itself, there are 10% or around 23.7 million children under five. Of this number, it can be estimated that around 1-3% of children under five in Indonesia experience growth and development problems. Developmental delays can be prevented through early detection and developmental stimulation. Early detection and stimulation of early childhood development by parents using the Developmental Pre-Screening Questionnaire (KPSP) for ages 3 to 72 months, carried out by parents, especially mothers, can help find the occurrence of child developmental deviations that must be handled immediately by competent health workers so that child development at each stage of their age can take place optimally. Early childhood midwifery care for An.I.E was carried out 3 visits involving mothers to conduct child development assessments using KPSP. The result was that the child was in the normal category. It is recommended for parents, teachers and competent health workers to monitor the child's development continuously so that they can detect deviations that occur